2021
DOI: 10.3390/cells11010010
|View full text |Cite|
|
Sign up to set email alerts
|

A Next Generation Sequencing-Based Protocol for Screening of Variants of Concern in Autism Spectrum Disorder

Abstract: Autism spectrum disorder (ASD) is a neurodevelopmental disorder with strong genetic influences. There is an increasing demand for ASD genetic testing beyond the traditionally recommended microarray and syndromic autism testing; however, the current whole genome sequencing (WGS) and whole exome sequencing (WES) methods are lacking an academic standard for WGS variant annotation, reporting, and interpretation, tailored towards patients with ASD and offer very limited interpretation for clinical significance. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…In the original publication [ 1 ], there was a mistake in Figure 1 as published. The authors have identified a typo in Figure 1 , which details the in-house variant annotation bioinformatics pipeline that was applied to screen for variants of concern.…”
mentioning
confidence: 99%
“…In the original publication [ 1 ], there was a mistake in Figure 1 as published. The authors have identified a typo in Figure 1 , which details the in-house variant annotation bioinformatics pipeline that was applied to screen for variants of concern.…”
mentioning
confidence: 99%